ChemInform Abstract: Identification of Six New Lupane‐Type Triterpenoids from Acanthopanax koreanum Leaves and Their Tyrosinase Inhibitory Activities. Issue 23 (May 2016) - Dat, Le Duc; Thao, Nguyen Phuong; Luyen, Bui Thi Thuy; Tai, Bui Huu; Jeong, Min Hee; Woo, Mi Hee; Kim, Young Ho
Abstract: Six new lupine‐type triterpenoids are isolated together with one new trihydroxylupane‐dioic acid derivative (III) and six already known compounds.